Invasive Strategy of STEMI in Patients with TAVB, RBBB, and Dual High-Risk Profiles: Navigating the Challenges of Antithrombotic Therapy – A Case Report - Shafira, Aisya Ayu; Hermawan, Hanestya Oky (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Background: It is imperative to diagnose and treat acute coronary occlusion as soon as possible, especially in patients with complicated conduction anomalies. Although electrocardiography (ECG) is still the gold standard for diagnosis, it has drawbacks, particularly when conduction abnormalities such as bundle branch block are present. Case Summary:  In this case study, a 60-year-old woman with cardiovascular risk factors and type 2 diabetes had an anteroseptal STEMI that was worsened by RBBB and total AV block. The patient's recovery was complicated by extensive gastrointestinal bleeding after a successful percutaneous coronary intervention (PCI) and the implantation of a stent in the left anterior descending artery. Conclusion: In addition to highlighting the difficulties of striking a balance between dual antiplatelet therapy (DAPT) and reperfusion strategies in a high bleeding risk setting, this also highlights the management of a high-risk STEMI patient with total atrioventricular (AV) block, right bundle branch block (RBBB), and severe gastrointestinal complications. -- Highlights: 1. This case illustrates the complex management of STEMI with total AV block and right bundle branch block, where urgent PCI and temporary pacing achieved rapid hemodynamic stabilization. 2. Post-PCI gastrointestinal bleeding under dual antiplatelet therapy highlights the need for individualized antithrombotic strategies and vigilant post-discharge monitoring in high-risk patients.